A COMBINED EFFECT OF ELECTROSTATIC FIELD AND HYDROSTATIC PRESSURE ON THE STABILITY OF BILAYER LIPID MEMBRANES - Gevorgyan, H. K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
The paper is devoted to the experimental research of bilayer lipid membranes stability (BLM) at joint action of an electrostatic field and hydrostatic pressure. It is shown, that with increase in a potential difference on BLM the average time of a life of a membrane decreases. Presence of hydrostatic pressure increasing leads to additional reduction of average time of the membrane life.
Keywords: BLM; lifetime; difference of potential; hydrostatic pressure